Resources and transversal competencies to reconcile child and parental responsibilities: A mini-review of the impact of COVID-19 on the Italian sandwich generation - Aurelia De Lorenzo; Lynda S. Lattke; Elga Zedda; Emanuela Rabaglietti (Tabriz University of Medical Sciences, 2023)
Background: The paper discusses the sandwich generation (SG) using a literature review approach. Longer life spans and the delayed economic and psychological independence of children mean that middle-aged parents find themselves caring for parents and children at the same period in their lives, at times this care may extend to grandchildren and grandparents. Results: The type of care varies depending on each person's need but also on the gender of the individual who looks after their parents while taking care of their own children. Cultural factors can also come into play. Conclusion: Complications in the lives of those who are part of the SG may arise affecting the quality of their time, their psyche, physical and financial situation. Having the necessary skills and strategies to cope with these complications is extremely important.